Actividades de comunicación infantil para desarrollar el lenguaje verbal de los niños y niñas de 3 a 4 años de la escuela de educación básica “Dr. Edison Calle Loaiza” de la ciudad de Loja periodo septiembre 2013 – julio 2014 - Guerrero Álvarez, Jenny del Rocío (2015)
The research work, called CHILD COMMUNICATION TO DEVELOP VERBAL LANGUAGE OF CHILDREN 3 TO 4 YEARS OF BASIC SCHOOL "DR. EDISON CALLE LOAIZA" FROM THE CITY OF LOJA PERIOD SEPTEMBER 2013 - JULY 2014 has been structured and developed in accordance with the regulations in force graduation from the National University of Loja whose purpose is to implement communications activities child in the everyday tasks of the teacher to better stimulate the development process of the oral language of children, reason by which the General Objective: Determine the communication activities child to develop verbal language of children 3 to 4 years at the school of basic education was raised "Dr. Edison Calle Loaiza" from the city of Loja period September 2013 - July 2014. The methods used were: analytical, historical, descriptive, synthetic, hermeneutical, inductive; techniques and instruments that are appliedp to the survey addressed teacher School "Dr. Loaiza Edison Street "and the test ZIMMERMAN - Scale preschool and school language aimed at children to assess Verbal Language Development. The sample is composed by 20 children 3 to 4 years and 1 teacher. Comprising a total of 21 people, of the results obtained through the Pearson correlation coefficient shows that Pearson's r is positive sign, which means that the alternative influences difficulties reducing them, emphasizing in this way the validity of child communication plan, which aims to develop the verbal language of the boys and girls from 3 to 4 years.